2009
DOI: 10.1111/j.1469-0691.2009.02895.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult invasive pneumococcal disease between 2003 and 2006 in North-Rhine Westphalia, Germany: serotype distribution before recommendation for general pneumococcal conjugate vaccination for children <2 years of age

Abstract: A laboratory-based surveillance study of adult invasive pneumococcal disease was conducted in North-Rhine Westphalia, Germany's most populous federal state, with approximately 18 million inhabitants. Invasive isolates (n = 519) were obtained between 2003 and 2006, before the general recommendation for vaccination of German children <2 years with the pneumococcal conjugate vaccine was issued at the end of July 2006. Penicillin G resistance was observed in 5% of meningitis cases. In the non-meningitis group, onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
2
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
2
6
2
5
Order By: Relevance
“…Overall, the most frequent serotypes were 14, 23F, 1, 6B, and 7F (in descending order), which is similar to the most frequent serotypes published in reports of other studies conducted over the same period in Germany (11,12). They deviate in part from older German data (17,20), but they are generally in line with the results reported from other countries (3,5,6,8,22,27).…”
Section: Discussionsupporting
confidence: 42%
“…Overall, the most frequent serotypes were 14, 23F, 1, 6B, and 7F (in descending order), which is similar to the most frequent serotypes published in reports of other studies conducted over the same period in Germany (11,12). They deviate in part from older German data (17,20), but they are generally in line with the results reported from other countries (3,5,6,8,22,27).…”
Section: Discussionsupporting
confidence: 42%
“…Surveillance systems (e.g. USActive Bacterial Core Surveillance Study [6], German Pneumococcus Surveillance Study [7]) rely on invasive isolates, because here the causality between pathogen and disease is easy to establish. However, in pneumococcal pneumonia, a positive blood culture only can be obtained in a minority of patients (,10%) [8].…”
mentioning
confidence: 99%
“…Therefore, surveillance of pneumococcal diseases on the basis of serotypes is essential, not only to learn about the current serotype pattern but also to observe the effectiveness of PCVs by following possible serotype changes in the population after vaccine introduction. In several studies, regional and temporal variations in serotype distribution were reported after PCV usage (6,7,(10)(11)(12). In this study, we aimed to identify serotypes of pneumococcal strains causing IPD in children in Turkey during the time period when PCV7 was newly included in the country's NIP.…”
mentioning
confidence: 99%